Anxiolytic-like effects of erythrinian alkaloids from erythrina suberosa - Serrano, Maria Amélia Rodrigues [UNESP]; De Luca Batista, Andrea Nastri [UNESP]; Da Silva Bolzani, Vanderlan [UNESP]; De Ávila Santos, Luciana [UNESP]; De Campos Nogueira, Paulo José [UNESP]; Nunes-De-Souza, Ricardo Luiz [UNESP]; Latif, Abdul; Arfan, Mohammad (My University, 2011)
Two alkaloids, erysodine (1) and erysothrine (2) were isolated from the flowers of a Pakistani medicinal plant, Erythrina suberosa. These compounds were investigated for anxiolytic properties, and the results showed significant effect, in an acute oral treatment with 1-2, which were suspended in saline (NaCl 0.9%) plus DMSO 1%, and evaluated in 122 Swiss male mice exposed to two tests of anxiety - the elevated plus-maze (EPM) and the light/dark transition model (LDTM).
Keywords: Anxyolitic activity; E. suberosa; Erythrinian alkaloids